Unix complete - Dyson, Peter (Sybex, 1999)
UNIX Complete is a one-of-a-kind computer book -- valuable both for its broad content and its low price. This book contains the essentials you need to know about using the popular operating system of universities and research centers, as well as at many Fortune 500 companies. Enormously powerful, UNIX is also complex enough to require that users first read a tutorial and then keep a reference handy for specialized commands.